Waliullahi Tehrik and its line of action for the revival and uplift of the Muslims in India (1731-1831) - Dr. Abid Hussain Associate; Dr. Syeda Sajida Batool; Dr. Mansoor Ahmed; Dr. Mohammad Dilshad Mohabbat (Corresponding Author) (Journal of Religion and Society, 2025)
Imam Shah Waliullah Dehlawi (RA) was the great sufi and janshīn of his father, Ḥaz͎rat Shah Abd-ur-Rahim Dehlawi (RA). So, he had to fulfill the responsibility of spiritual training of disciples of the khaqah after the death of his father. Moreover, he also administered his father’s established Madrasah Rahīmiyah. He observed both the rise and fall of the Muslims in the Subcontinent because the decline of the Mughals had started in his life. He established his jamā ‘t, and introduced a clear and complete system of thoughts and philosophy to get rid of decline. After him, Ḥaz͎rat Shah Abd-ul-Aziz (RA) and Ḥaz͎rat Shah Iahaq Dehlawi (RA) continued the struggle and followed the same line of action, set by Ḥaz͎rat Shah Waliullah Dehalwi (RA). Most of the religious and religio-political groups in Pakistan associate themselves with Imam Shah Waliullahi Dehlawi (RA) and his movement in order to strengthen their intellectual superiority, religious identity and historical legitimacy. This research attempts to explore the footprints and line of action of Walīullāhi Tehrīk, and how it played its role for the revival and uplift of the Muslims. Following the historical research method, the data was collected from different sources, including the writings and biographies of Walīullāhi Ulama. The data analysis shows that Walīullāhi Mashaikh served in three spheres of Shari‘at, Tarīqat and Politics. Key Words: Walīullāhi Tehrīk, Shah Waliullah Dehlawi, Madrasah Rahīmiyah, Political Role